2013
DOI: 10.1128/aem.03608-12
|View full text |Cite
|
Sign up to set email alerts
|

Contact Killing of Bacteria on Copper Is Suppressed if Bacterial-Metal Contact Is Prevented and Is Induced on Iron by Copper Ions

Abstract: bBacteria are rapidly killed on copper surfaces, and copper ions released from the surface have been proposed to play a major role in the killing process. However, it has remained unclear whether contact of the bacteria with the copper surface is also an important factor. Using laser interference lithography, we engineered copper surfaces which were covered with a grid of an inert polymer which prevented contact of the bacteria with the surface. Using Enterococcus hirae as a model organism, we showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
114
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 43 publications
8
114
1
1
Order By: Relevance
“…The second important requirement for contact killing is bacterial contact with the metal surface (16). Recently, we showed that bacteria are also killed effectively on iron surfaces if ionic copper ions are present (16). In the present study, we also show that the reduction of Cu 2ϩ to Cu ϩ by the iron surface plays a key role in the killing process.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The second important requirement for contact killing is bacterial contact with the metal surface (16). Recently, we showed that bacteria are also killed effectively on iron surfaces if ionic copper ions are present (16). In the present study, we also show that the reduction of Cu 2ϩ to Cu ϩ by the iron surface plays a key role in the killing process.…”
supporting
confidence: 60%
“…Bacterial copper resistance systems appear unable to cope with the released copper (13)(14)(15). The second important requirement for contact killing is bacterial contact with the metal surface (16). Recently, we showed that bacteria are also killed effectively on iron surfaces if ionic copper ions are present (16).…”
mentioning
confidence: 99%
“…This effect has been demonstrated for bacteria such as pathogenic Escherichia coli strains (4), Pseudomonas aeruginosa (5), methicillin-resistant Staphylococcus aureus (6), Burkholderia cepacia (7), and Salmonella enterica (8), as well as for viruses (9,10) and yeasts (11). Copper ions need to be released from the copper surfaces to mediate the killing process (12,13), and there has to be direct contact between the cell and the copper surface (14). Therefore, a variety of parameters influence the success of the inactivation process by interfering with copper release and the availability of the copper ions for the killing action: (i) temperature, (ii) humidity, (iii) ionization/corrosion, (iv) the dry/ wet test protocol used, and (v) the content of organic material (6,15,16).…”
mentioning
confidence: 99%
“…The limited data so far available suggest only modest antimicrobial action. Mathews et al emphasized the need of the bacteria to be in contact with the copper if killing is to occur [27]. Nevertheless, the polyacrylic material used in NanoCote HD-WR may be sufficiently permeable to allow copper to be present at the surface on which the bacteria will arrive.…”
Section: Coefficients Of Friction In the Wet And Dry Statesmentioning
confidence: 99%
“…In recent years considerable progress has been made towards elucidating the bactericidal mechanism of copper [21][22][23][24][25][26][27]. There is no need to discuss it here, 1 other than to remark that the release of copper ions from the surface is required, hence the encapsulation matrix should be chosen so as to allow their (slow) release.…”
Section: Disastrous Performance Of Nanocote/aqua Based Antimicrobial mentioning
confidence: 99%